Fostering emotional intelligence in preadolescence: Effects of a pilot training on emotions, coping and psychological well-being. (April 2023) - Pauletto, Marina; Grassi, Michele; Pellizzoni, Sandra; Penolazzi, Barbara
The purpose of the present study was to examine the efficacy of a short training programme (eight 1-hour sessions) aimed to promote Emotional Intelligence (EI) abilities in primary school on a set of outcomes related to affect, coping and psychological well-being. Sixty-eight preadolescents (10.68±.58 years) were randomly assigned to either the experimental condition (EI training) or the active control condition (pro-environmental training). ANOVAs and Bayesian analyses were performed on pre/post-training measures of ability and trait EI, positive/negative affect, regulatory emotional self-efficacy, coping styles, and psychological well-being. Results showed that only in the EI training condition emotional abilities significantly improved, whereas negative affect and the preference for distraction coping significantly diminished. Although the effects of the present EI training did not extend to the other measures, the findings suggest its effectiveness in improving preadolescents' EI basic skills and some important adjustment variables. This study confirms the efficacy of short school-based programmes in enhancing EI abilities and highlights the importance of further investigating the training features required to extend its benefits also to psychological well-being. Implications for research and educational practices are discussed.